Molecular Identification of Anisakis Species (Nematoda: Anisakidae) From Marine Fishes Collected in Turkish Waters - Pekmezci, Gökmen Zafer; Onuk, E.E.; Bölükbaş, C.S.; Yardimci, B.; Gürler, A.T.; Açıcı, M.; Umur, S. (Elsevier Science B.V., 2014)
Anisakid nematodes are important etiological agents for zoonotic human anisakiasis (or anisakidosis). These parasites in the Turkish waters still remain unexplored. This study aims the molecular identification of Anisakis species in Turkey's coast from Black, Aegean and Mediterranean Sea and specifically to screen for zoonotic species in commonly commercialized a total of 1145 fish belonging to 31 different species using both polymerase chain reaction-restriction fragment length polymorphism analysis (PCR-RFLP) and sequencing of the ribosomal internal transcribed spacer (ITS) regions and the mitochondrial cytochrome C oxidase subunit II (cox2) gene. A total of 776 Anisakis type I larvae were isolated in 56/1145 (4.8%) fish of 7 species from Turkish waters. The combining all of our results, e.g., morphology, PCR-RFLP, ITS region, and the cox2 gene, conclusively supported the identification of 3 Anisakis spp. taken from marine fish hosts, namely Anisakis pegreffii, Anisakis typica and Anisakis simplex sensu stricto (s.str.)/. A. pegreffii hybrid genotype. No Anisakis larvae were isolated from the Black Sea whereas A. pegreffii, A. typica and A. simplex s.str./. A. pegreffii hybrid genotype was found in the Aegean Sea and A. pegreffii was only isolated from the Mediterranean Sea. This study represents the first identification of A. typica and A. simplex s.str./. A. pegreffii hybrid genotypes from Turkish waters. Moreover, in the present study first record of the presence of A. pegreffii is also reported from Turkish coasts of Aegean and Mediterranean Sea. No zoonotic Anisakis species were found in commonly commercialized 1025 fish belonging to 16 different species from the Black Sea, thus Turkish populations who consume captured fish from the Black Sea may have a less risk of human anisakiasis or allergies. However, the prevalence of larvae were 47.1% and 46% and recognized zoonotic A. pegreffii were identified from the Aegean and Mediterranean Sea coast, suggesting a high threat of anisakiasis or allergies for Turkish populations who consume fish originating in these regions. © 2014 Elsevier B.V.
Keywords: Anisakis Species; Cox2 Gene; ITS Region; PCR-RFLP; Sequencing; Turkish Waters